Skyping the Family : Interpersonal Video Communication and Domestic Life. - Harper, Richard; Watson, Rod.; Licoppe, Christian (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2019)
This collection is one of the first in-depth studies of video calling in family and domestic life. Originally published as a special issue of Pragmatics, issue 27:3 (2017).
Intro -- Skyping the Family -- Editorial page -- Title page -- Copyright page -- Table of contents -- Interpersonal video communication as a site of human sociality -- 1. Background -- 2. Perspectives on mediated communications -- 3. The need for a different approach -- 4. Evidence from within -- 5. Overview of the book -- References -- Authors' addresses -- The 'interrogative gaze': Making video calling and messaging 'accountable' -- 1. Introduction -- 2. Approach to evidence -- 3. Evidence in everyday reasoning about Skype -- 4. Why Skype? -- 5. Conclusions -- References -- Authors' addresses -- Skype appearances, multiple greetings and 'coucou': The sequential organization of video-mediated conversation openings -- 1. Introduction -- 2. Analysis -- 3. Conclusion -- References -- Author's address -- Talking about things: Image-based topical talk and intimacy in video-mediated family communication -- 1. Introduction -- 2. Background: Topical talk -- 3. Showings as visual turn taking in storytelling between relatives -- 4. Noticings as intimacy achieving practices -- 5. Conclusion -- References -- Appendix. Transcription conventions -- Authors' addresses -- Showing 'digital' objects in web-based video chats as a collaborative achievement -- 1. Introduction -- 2. Hangouts On Air -- 3. Conclusion -- References -- Authors' addresses -- The Skype paradox: Homelessness and selective intimacy in the use of communications technology -- 1. Introduction -- 2. Analysis -- 3. Conclusion: Reasons, causes, evidentiality -- References -- Authors' addresses -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books